2022
DOI: 10.1021/acs.jpcc.2c03996
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Tunable Effects of Single Metal Atoms Supported on Nitrogen-Doped Carbon Nanotubes during NO Oxidation from Microkinetic Simulation

Abstract: NO oxidation is one of the most used catalytic routes for NO x removal, which is a pressing environmental issue. As an emerging new class of catalysts, single atom catalysts (SACs) have demonstrated competitive catalytic capabilities compared with conventional noble metals regarding NO oxidation. It is of pivotal importance to understand the working principle and screen the best candidate SAC in NO oxidation. To this end, five SACs (Fe, Co, Ni, Cu, and Pt) have been examined and compared, which exhibit unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Although its oxidation energy barrier is only 0.17 eV, its NO 2 desorption energy barrier is 1.5 eV, which also limits the reaction activity of the catalytic process. Si et al 19 conducted research on the oxidation of NO by O 2 using five SACs (Fe, Co, Ni, Cu, and Pt). Their findings revealed that nitrogen doping agents effectively modulate the electronic structure of metal active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Although its oxidation energy barrier is only 0.17 eV, its NO 2 desorption energy barrier is 1.5 eV, which also limits the reaction activity of the catalytic process. Si et al 19 conducted research on the oxidation of NO by O 2 using five SACs (Fe, Co, Ni, Cu, and Pt). Their findings revealed that nitrogen doping agents effectively modulate the electronic structure of metal active sites.…”
Section: Introductionmentioning
confidence: 99%